Original paperA link between the outcome of living unrelated kidney transplantation and HLA compatibility: a preliminary report - Pourfarziani, Vahid; Einollahi, Behzad; Assari, Shervin; Kardavani, Babak; Lankarani, Maryam Moghani; Kalantar, Ebrahim (Archives of Medical Science, 2007)
Introduction: Within the different variables affecting renal allograft outcome in the case of HLA matching, there is continued controversy. There are very few studies regarding this issue in grafts from living unrelated donors (LURDs). We aim to assess the impact of HLA compatibility on genetically unrelated renal transplantation. Material and methods: Four hundred and one kidney grafts from LURDs were analyzed. The transplantation procedures were performed in Baqiyatallah hospital, Tehran, Iran, during the period between 1999 and 2002. HLA-A, -B and -DR loci were typed with PCR techniques both in donors and recipients. Based on the number of HLA mismatches, we grouped patients to Group I (0-4 HLA mismatches) and Group II (5-6 HLA mismatches). Three-year graft survival rates were compared in the study groups. Results: From 358 pairs of donors and recipients, 242 (67.6%) had 0-4 and 116 (32.4%) pairs had 5-6 HLA-A-B-DR mismatches. The groups were not significantly different in terms of donor and recipient age difference, donor and recipient gender, ischemia time, follow-up time, and cyclosporine dose. Three-year graft survival was 83% for recipients with 0-4 HLA mismatches and 54% for those with 5-6 mismatches (p=0.001). Three-year graft survival was 83% and 54% for those recipients with 0 and 1-2 mismatches in HLA-A respectively (p=0.014), 77% and 64% for those with 0 and 1-2 mismatches in HLA-B respectively (p=0.029), and 74% and 62% for those with 0 and 1-2 mismatches in HLA-DR respectively (p=0.003). From the variables, including number of HLA mismatches, donor and recipient age and HCV infection, that significantly affect 3-year graft survival, all except donor age remained significant in the model. Conclusions: Number of HLA mismatches, along with other variables including age of recipient and HCV infection, significantly affects survival of the allograft. If the result of this preliminary report is confirmed by future studies, the use of graft with a lower number of mismatches will be recommended for use, regardless of the type of allele.